A Realm of Mere Representation? “Live” E-Sports Spectacles and the Crafting of China’s Digital Gaming Image - Szablewicz, Marcella (Games and Culture, 2016)
This article addresses the proliferation of images and appearances in the realm of e-sports culture in urban China. The author’s findings are based upon ethnographic research and participant observation of e-sports audience members, teams, and tournaments, including the 2010 E-sports Champion League tournament in Beijing, the 2012 and 2013 World Cyber Games Festivals in Kunshan, and a 2014 Starcraft II tournament in Shanghai. A comparison of these events leads the author to argue that live e-sports events in China are less about spectatorship than they are about creating a spectacle that presents a carefully crafted vision of Chinese politics, nationalism, and capitalist consumer culture. In these cases, the participants and audience members are not only commodities to be sold but also a means of masking contradictory and highly ambivalent discourses about China’s role in technological production, digital game culture, and the promotion of the discourse of Internet addiction.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé